Valuasi Ekonomi Objek Wisata Berbasis Jasa Lingkungan Menggunakan Metode Biaya Perjalanan di Pantai Batu Karas Kabupaten Pangandaran - FIRMAN ZULPIKAR; DANDY E. PRASETIYO; TITIS VIRGININDA SHELVATIS; KINTA KARISSA KOMARA; MONICA PRAMUDAWARDHANI (P4W LPPM IPB, 2017)
Batu Karas beach at Pangandaran Regency, West Java Province has the potential of natural beauties that can be used as an ecotourism object. The purpose of this study was to determine the economic value of environmental service-based tourism and to identify factors that contribute to the tourism demand to Batu Karas beach. Individual Travel Cost Method (ITCM) was used to estimate the potential economic value of tourism activity, and linear regression analysis was used to determine the influence factors of tourism demand. Data was obtained through questionnaires to respondents. The results showed that the most influential factors of the level of tourist demand to Batu Karas beach are travel cost, distance and duration in the location. The demand equation model based on travel cost method is Y = 1.766 ???? 0.000001887 X1 ; where Y= tourism demand and X1 = travel cost. Potential economic value of ecotourism in Batu Karas beach reached Rp 86,571,960,874.00 annually with a consumer surplus of Rp 566,183.00 per individual per year. Major economic benefits from tourism activities in Batu Karas beach brings socio-economic improvement of the local community.